Bio-based waterproof coating
Through a combination of specific processes and materials, bio-based waterproof coatings with excellent flame retardant and waterproof properties are prepared, which solves the problem of insufficient performance in the prior art and meets higher market demand.
Patent Information
- Application Number
- CN202411480734.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The flame retardant and mechanical properties of existing bio-based waterproof coatings are insufficient, making it difficult to meet higher quality and market demand.
Using a specific proportion of coating base, functional filler, synergistic filler, catalyst, curing agent and antioxidant combination, bio-based waterproof coatings are prepared through specific process flow, including palm oil, formic acid, hydrogen peroxide, glycol, The treatment and mixing of itaconic acid, wheat straw, r-aminopropyltriethoxysilane, bentonite, nanosilica and nanographene oxide can form a coating with excellent flame retardant and waterproofing properties.
It significantly improves the mechanical properties and flame retardant properties of bio-based waterproof coatings, ensures their quality and quality, and is suitable for a wider market application.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating production, in particular to a bio-based waterproof coating. Background Art
[0002] Waterproof coatings are solvent-based, water-based or powder-based coatings made of synthetic high molecular polymers as the main film-forming substances, and various additives, modified materials, and filling materials. The coatings are applied to the roofs, basements, toilets, bathrooms, and exterior walls of buildings that need to be waterproofed, and can form a continuous, integrated, and certain-thick coating waterproof layer at room temperature.
[0003] In the patent document with application number "CN202311802289.4" and name "A bio-based waterproof coating, preparation method and application thereof", it is recorded that "The waterproof coating includes the following ingredients: Component A: According to the total weight of component A, 20-60% of bio-based polyol, 5-40% of diluent, 10-70% of filler, 0-5% of colorant, 0.01-2% of defoaming agent, and 0.01-2% of catalyst; Component B: According to the total weight of component B, 100% of curing agent. The weight ratio of component A to component B is (5-12): 1. By optimizing the types and relative amounts of components A and B, the performance of bio-based waterproof coatings in waterproofing and anti-seepage, workability, crack resistance, bonding strength, temperature resistance, chemical resistance, etc. can be improved, and the material is more environmentally friendly and can be used for waterproofing of water-facing surfaces."
[0004] Although the bio-based waterproof coating produced by the above patent document has certain advantages such as waterproofing, its flame retardancy and mechanical properties are relatively insufficient and still need to be further improved. Based on this, the present invention provides a bio-based waterproof coating to solve the above technical problems. Summary of the invention
[0005] The purpose of the present invention is to provide a bio-based waterproof coating. The prepared bio-based waterproof coating not only has good mechanical properties, but also has excellent flame retardant and waterproof properties, effectively ensuring its quality.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a bio-based waterproof coating, which is composed of the following raw materials in parts by weight: 20 to 30 parts of coating base, 3 to 6 parts of functional fillers, 3 to 5 parts of synergistic fillers, 2 to 4 parts of o-cresyl glycidyl ether, 2 to 4 parts of catalyst CUCAT-PD, 3 to 5 parts of curing agent and 2 to 5 parts of antioxidant.
[0008] The present invention is further configured as follows: the preparation process of the coating base material is as follows:
[0009] Palm oil, formic acid and hydrogen peroxide are placed in a stirring device at a mass ratio of 1:0.21-0.25:0.45-0.55, treated at 55-60°C for 6-7 hours, and after solid-liquid separation, vacuum distillation is performed to obtain a preliminary product;
[0010] The preliminary product and ethylene glycol are placed in a mixing device at a mass ratio of 1:0.7-0.9, and itaconic acid is added thereto. The mixture is stirred at 22-32°C and 80-110 r / min for 20-30 minutes, and then the temperature is raised to 140-150°C and constant temperature treatment is performed for 120-130 minutes to prepare a coating base material.
[0011] The present invention is further configured as follows: the addition amount of the itaconic acid is 3.2-3.5% of the mass of the base material.
[0012] The present invention is further configured as follows: the preparation process of the functional filler is as follows:
[0013] The wheat straw is soaked in a sodium hydroxide aqueous solution with a mass concentration of 5.2-6.2% for 22-24 hours, then washed with deionized water for 2-6 times, and dried to obtain pretreated wheat straw;
[0014] r-aminopropyltriethoxysilane is placed in a 90% ethanol aqueous solution at a mass ratio of 1:8-10, and stirred at 100-120 r / min for 20-30 minutes to obtain a mixed solution, and then the composite material is added to the mixed solution, and ultrasonic treatment is performed for 30-40 minutes;
[0015] Then, the pretreated wheat straw is added, and the ultrasonic treatment is continued for 25 to 35 minutes. After filtration, the mixture is dried and crushed to obtain a functional filler.
[0016] The present invention is further configured as follows: the composite material is formed by mixing nano silicon dioxide and nano graphene oxide in a mass ratio of 1:0.2 to 0.4.
[0017] The present invention is further configured as follows: the addition amount of the composite material is 12-16% of the mass of the mixed liquid.
[0018] The present invention is further configured as follows: the preparation process of the synergistic filler is as follows:
[0019] The bentonite is soaked in water for 50 to 60 minutes, filtered, dried to constant weight, and then placed in a resistance furnace, calcined at 510 to 530° C. for 120 to 140 minutes, cooled to 80° C., and kept warm for 40 minutes to obtain pretreated bentonite;
[0020] The pretreated bentonite is placed in a sodium tripolyphosphate solution with a mass concentration of 12-14% at a solid-liquid ratio of 0.2-0.8 g / mL and mixed evenly, and allowed to stand at 70° C. for 80-100 minutes. After filtration, the solution is dried to constant weight to obtain a synergistic filler.
[0021] The present invention is further configured as follows: the curing agent is selected from any one of toluene diisocyanate and diphenylmethane diisocyanate.
[0022] The present invention is further configured as follows: the antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.
[0023] The second aspect of the present invention: also provides the preparation process of the above-mentioned bio-based waterproof coating as follows:
[0024] Step 1: Accurately weigh the coating base material, functional filler, synergistic filler, o-cresyl glycidyl ether, catalyst CUCAT-PD, curing agent and antioxidant;
[0025] Step 2: Place the coating base material, functional filler, synergistic filler, o-cresyl glycidyl ether and catalyst CUCAT-PD in a mixing device and mix them evenly to obtain a first mixture;
[0026] Step 3, mixing the curing agent and the antioxidant evenly to obtain a second mixture;
[0027] Step 4: Mix the first mixture and the second mixture to obtain a bio-based waterproof coating.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] In the present invention, a coating base material, a functional filler, a synergistic filler, o-cresyl glycidyl ether, a catalyst CUCAT-PD, a curing agent and an antioxidant are used as raw materials. The coating base material, the functional filler, the synergistic filler, o-cresyl glycidyl ether and the catalyst CUCAT-PD are placed in a mixing device and mixed evenly to obtain a first mixture, and then the curing agent and the antioxidant are mixed evenly to obtain a second mixture. Finally, the first mixture and the second mixture are mixed to obtain a bio-based waterproof coating. The bio-based waterproof coating prepared by the present invention not only has good mechanical properties, but also has excellent flame retardant and waterproof properties, which effectively guarantees its quality. The bio-based waterproof coating provided by the present invention has a broader market prospect and is more suitable for promotion. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] The present embodiment provides a bio-based waterproof coating, which is composed of the following raw materials in parts by weight: 20 parts of coating base, 3 parts of functional filler, 3 parts of synergistic filler, 2 parts of o-cresyl glycidyl ether, 2 parts of catalyst CUCAT-PD, 3 parts of curing agent and 2 parts of antioxidant.
[0033] Among them, the preparation process of the coating base material is as follows:
[0034] Palm oil, formic acid and hydrogen peroxide were placed in a stirring device at a mass ratio of 1:0.21:0.45, treated at 55°C for 6 hours, and after solid-liquid separation, vacuum distillation was performed to obtain a preliminary product;
[0035] The preliminary product and ethylene glycol were placed in a mixing device at a mass ratio of 1:0.7, and itaconic acid was added thereto. The mixture was stirred at 22°C and 80 r / min for 20 minutes, and then the temperature was raised to 140°C and the mixture was kept at a constant temperature for 120 minutes to prepare a coating base.
[0036] Furthermore, the addition amount of itaconic acid is 3.2% of the mass of the base material.
[0037] In this embodiment, it should be noted that palm oil was purchased from Shaanxi Xiazhou Biotechnology Co., Ltd.
[0038] At the same time, the preparation process of functional fillers is as follows:
[0039] The wheat straw was immersed in a sodium hydroxide aqueous solution with a mass concentration of 5.2% for 22 hours, then washed twice with deionized water, and dried to obtain pretreated wheat straw;
[0040] r-aminopropyltriethoxysilane was placed in a 90% ethanol aqueous solution at a mass ratio of 1:8, and stirred at 100 r / min for 20 minutes to obtain a mixed solution, and then the composite material was added to the mixed solution, and ultrasonic treatment was performed for 30 minutes;
[0041] Then the pretreated wheat straw was added, and the ultrasonic treatment was continued for 25 minutes. After filtration, the mixture was dried and crushed to obtain a functional filler.
[0042] Furthermore, the composite material is formed by mixing nano silicon dioxide and nano graphene oxide in a mass ratio of 1:0.2.
[0043] The amount of the compound added is 12% of the mass of the mixed liquid.
[0044] In this embodiment, it should be noted that nano-silicon dioxide was purchased from Shijiazhuang Fengming Mineral Products Co., Ltd., and nano-graphene oxide was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd.
[0045] The preparation process of the synergistic filler is as follows:
[0046] The bentonite was soaked in water for 50 minutes, filtered, dried to constant weight, and then placed in a resistance furnace, calcined at 510° C. for 120 minutes, cooled to 80° C., and kept warm for 40 minutes to obtain pretreated bentonite;
[0047] The pretreated bentonite was placed in a sodium tripolyphosphate solution with a mass concentration of 12% at a solid-liquid ratio of 0.2 g / mL, mixed evenly, and allowed to stand at 70° C. for 80 minutes. After filtration, the solution was dried to constant weight to obtain a synergistic filler.
[0048] In this embodiment, it should be noted that the bentonite was purchased from Sishui County Hengjian Bentonite Co., Ltd.
[0049] Toluene diisocyanate is used as the curing agent.
[0050] The antioxidant used is antioxidant 1010.
[0051] In addition, this embodiment also provides the preparation process of the above-mentioned bio-based waterproof coating as follows:
[0052] Step 1: Accurately weigh the coating base material, functional filler, synergistic filler, o-cresyl glycidyl ether, catalyst CUCAT-PD, curing agent and antioxidant;
[0053] Step 2: Place the coating base material, functional filler, synergistic filler, o-cresyl glycidyl ether and catalyst CUCAT-PD in a mixing device and mix them evenly to obtain a first mixture;
[0054] Step 3, mixing the curing agent and the antioxidant evenly to obtain a second mixture;
[0055] Step 4: Mix the first mixture and the second mixture to obtain a bio-based waterproof coating.
[0056] Example 2
[0057] The present embodiment provides a bio-based waterproof coating, which is composed of the following raw materials in parts by weight: 25 parts of coating base, 4 parts of functional filler, 4 parts of synergistic filler, 3 parts of o-cresyl glycidyl ether, 3 parts of catalyst CUCAT-PD, 4 parts of curing agent and 3 parts of antioxidant.
[0058] Among them, the preparation process of the coating base material is as follows:
[0059] Palm oil, formic acid and hydrogen peroxide were placed in a stirring device at a mass ratio of 1:0.23:0.5, treated at 57°C for 7 hours, and after solid-liquid separation, vacuum distillation was performed to obtain a preliminary product;
[0060] The preliminary product and ethylene glycol were placed in a mixing device at a mass ratio of 1:0.8, and itaconic acid was added thereto. The mixture was stirred at 27°C and 95 r / min for 25 minutes, and then the temperature was raised to 145°C and the mixture was kept at a constant temperature for 125 minutes to prepare a coating base.
[0061] Furthermore, the addition amount of itaconic acid is 3.3% of the base material mass.
[0062] In this embodiment, it should be noted that palm oil was purchased from Shaanxi Xiazhou Biotechnology Co., Ltd.
[0063] At the same time, the preparation process of functional fillers is as follows:
[0064] The wheat straw was immersed in a sodium hydroxide aqueous solution with a mass concentration of 5.7% for 23 hours, then washed with deionized water for 4 times, and dried to obtain pretreated wheat straw;
[0065] r-aminopropyltriethoxysilane was placed in a 90% ethanol aqueous solution at a mass ratio of 1:9, and stirred at 110 r / min for 25 minutes to obtain a mixed solution, and then the composite material was added to the mixed solution, and ultrasonic treatment was performed for 35 minutes;
[0066] Then the pretreated wheat straw was added, and the ultrasonic treatment was continued for 30 minutes. After filtration, the mixture was dried and crushed to obtain a functional filler.
[0067] Furthermore, the composite material is formed by mixing nano silicon dioxide and nano graphene oxide in a mass ratio of 1:0.3.
[0068] The amount of the compound added is 14% of the mass of the mixed liquid.
[0069] In this embodiment, it should be noted that nano-silicon dioxide was purchased from Shijiazhuang Fengming Mineral Products Co., Ltd., and nano-graphene oxide was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd.
[0070] The preparation process of the synergistic filler is as follows:
[0071] The bentonite was soaked in water for 55 minutes, filtered, dried to constant weight, and then placed in a resistance furnace, calcined at 520° C. for 130 minutes, cooled to 80° C., and kept warm for 40 minutes to obtain pretreated bentonite;
[0072] The pretreated bentonite was placed in a sodium tripolyphosphate solution with a mass concentration of 13% at a solid-liquid ratio of 0.5 g / mL, mixed evenly, and allowed to stand at 70° C. for 90 minutes. After filtration, the solution was dried to constant weight to obtain a synergistic filler.
[0073] In this embodiment, it should be noted that the bentonite was purchased from Sishui County Hengjian Bentonite Co., Ltd.
[0074] The curing agent is diphenylmethane diisocyanate.
[0075] Antioxidant 1076 was selected as the antioxidant.
[0076] In addition, this embodiment also provides the preparation process of the above-mentioned bio-based waterproof coating as follows:
[0077] Step 1: Accurately weigh the coating base material, functional filler, synergistic filler, o-cresyl glycidyl ether, catalyst CUCAT-PD, curing agent and antioxidant;
[0078] Step 2: Place the coating base material, functional filler, synergistic filler, o-cresyl glycidyl ether and catalyst CUCAT-PD in a mixing device and mix them evenly to obtain a first mixture;
[0079] Step 3, mixing the curing agent and the antioxidant evenly to obtain a second mixture;
[0080] Step 4: Mix the first mixture and the second mixture to obtain a bio-based waterproof coating.
[0081] Example 3
[0082] The present embodiment provides a bio-based waterproof coating, which is composed of the following raw materials in parts by weight: 30 parts of coating base, 6 parts of functional filler, 5 parts of synergistic filler, 4 parts of o-cresyl glycidyl ether, 4 parts of catalyst CUCAT-PD, 5 parts of curing agent and 5 parts of antioxidant.
[0083] Among them, the preparation process of the coating base material is as follows:
[0084] Palm oil, formic acid and hydrogen peroxide were placed in a stirring device at a mass ratio of 1:0.25:0.55, treated at 60°C for 7 hours, and after solid-liquid separation, vacuum distillation was performed to obtain a preliminary product;
[0085] The preliminary product and ethylene glycol were placed in a mixing device at a mass ratio of 1:0.9, and itaconic acid was added thereto. The mixture was stirred at 32°C and 110 r / min for 30 minutes, and then the temperature was raised to 150°C and kept at a constant temperature for 130 minutes to prepare a coating base.
[0086] Furthermore, the addition amount of itaconic acid is 3.5% of the base material mass.
[0087] In this embodiment, it should be noted that palm oil was purchased from Shaanxi Xiazhou Biotechnology Co., Ltd.
[0088] At the same time, the preparation process of functional fillers is as follows:
[0089] The wheat straw was immersed in a sodium hydroxide aqueous solution with a mass concentration of 6.2% for 24 hours, then washed with deionized water for 6 times, and dried to obtain pretreated wheat straw;
[0090] r-aminopropyltriethoxysilane was placed in a 90% ethanol aqueous solution at a mass ratio of 1:10, and stirred at 120 r / min for 30 min to obtain a mixed solution, and then the composite material was added to the mixed solution, and ultrasonic treatment was performed for 40 min;
[0091] Then the pretreated wheat straw was added, and the ultrasonic treatment was continued for 35 minutes. After filtration, the mixture was dried and crushed to obtain a functional filler.
[0092] Furthermore, the composite material is formed by mixing nano silicon dioxide and nano graphene oxide in a mass ratio of 1:0.4.
[0093] The amount of the compound added is 16% of the mass of the mixed liquid.
[0094] In this embodiment, it should be noted that nano-silicon dioxide was purchased from Shijiazhuang Fengming Mineral Products Co., Ltd., and nano-graphene oxide was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd.
[0095] The preparation process of the synergistic filler is as follows:
[0096] The bentonite was soaked in water for 60 minutes, filtered, dried to constant weight, and then placed in a resistance furnace, calcined at 530° C. for 140 minutes, cooled to 80° C., and kept warm for 40 minutes to obtain pretreated bentonite;
[0097] The pretreated bentonite was placed in a sodium tripolyphosphate solution with a mass concentration of 14% at a solid-liquid ratio of 0.8 g / mL and mixed evenly, and allowed to stand at 70° C. for 100 minutes. After filtration, the solution was dried to constant weight to obtain a synergistic filler.
[0098] In this embodiment, it should be noted that the bentonite was purchased from Sishui County Hengjian Bentonite Co., Ltd.
[0099] Toluene diisocyanate is used as the curing agent.
[0100] The antioxidant used is antioxidant CA.
[0101] In addition, this embodiment also provides the preparation process of the above-mentioned bio-based waterproof coating as follows:
[0102] Step 1: Accurately weigh the coating base material, functional filler, synergistic filler, o-cresyl glycidyl ether, catalyst CUCAT-PD, curing agent and antioxidant;
[0103] Step 2: Place the coating base material, functional filler, synergistic filler, o-cresyl glycidyl ether and catalyst CUCAT-PD in a mixing device and mix them evenly to obtain a first mixture;
[0104] Step 3, mixing the curing agent and the antioxidant evenly to obtain a second mixture;
[0105] Step 4: Mix the first mixture and the second mixture to obtain a bio-based waterproof coating.
[0106] Comparative Example 1: The difference from Example 1 is that in this example, an equal amount of aliphatic dimer alcohol (BASF, model number Sovermol908) is used to replace the coating base material.
[0107] Comparative Example 2: The difference from Example 1 is that this example does not contain functional fillers.
[0108] Comparative Example 3: The difference from Example 1 is that this example does not contain a synergistic filler.
[0109] Performance test: The bio-based waterproof coating samples provided in Examples 1 to 3 and Comparative Examples 1 to 3 are marked as Examples 1 to 3 and Comparative Examples 1 to 3, respectively; and the relevant properties of the bio-based waterproof coatings provided in Examples 1 to 3 and Comparative Examples 1 to 3 are tested as follows:
[0110] 1. Tensile strength test: The test method is: GB / T16777-2008.
[0111] 2. Waterproof test: The test method is: GB / T16777-2008 (0.3Mp, 120min).
[0112] 3. Flame retardant test: The test method is: ISO4589-1984 for oxygen index determination (strip size 130.0mm×6.5mm×3mm).
[0113] The obtained test data are recorded in Tables 1 to 3 below:
[0114] Table 1 Mechanical properties test results of each group of bio-based waterproof coatings
[0115] Group Tensile strength(MPa) Example 1 Group 10.5 Example 2 Group 10.2 Example 3 Group 10.4 Comparison group 1 7.2 Comparison of 2 groups 6.8 Comparison of 3 groups 8.8
[0116] Table 2 Waterproof performance test results of each group of bio-based waterproof coatings
[0117] Group Waterproof Example 1 Group impermeable Example 2 Group impermeable Example 3 Group impermeable Comparison group 1 permeable Comparison of 2 groups permeable Comparison of 3 groups impermeable
[0118] Table 3 Flame retardant test results of each group of bio-based waterproof coatings
[0119] Group Oxygen Index Example 1 Group 31 Example 2 Group 30 Example 3 Group 32 Comparison group 1 28 Comparison of 2 groups 25 Comparison of 3 groups 22
[0120] By comparing and analyzing the relevant data in Tables 1 to 3, it can be seen that the bio-based waterproof coating prepared by the present invention not only has good mechanical properties, but also has excellent flame retardant and waterproof properties, effectively ensuring its quality. This shows that the bio-based waterproof coating provided by the present invention has a broader market prospect and is more suitable for promotion.
[0121] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0122] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Bio-based waterproof coating, characterized in that: The invention is composed of the following raw materials in parts by weight: 20 to 30 parts of coating base material, 3 to 6 parts of functional filler, 3 to 5 parts of synergistic filler, 2 to 4 parts of o-cresyl glycidyl ether, 2 to 4 parts of catalyst CUCAT-PD, 3 to 5 parts of curing agent and 2 to 5 parts of antioxidant; The preparation process of the bio-based waterproof coating is as follows: Step 1: Accurately weigh the coating base material, functional filler, synergistic filler, o-cresyl glycidyl ether, catalyst CUCAT-PD, curing agent and antioxidant; Step 2: Place the coating base material, functional filler, synergistic filler, o-cresyl glycidyl ether and catalyst CUCAT-PD in a mixing device and mix them evenly to obtain a first mixture; Step 3, mixing the curing agent and the antioxidant evenly to obtain a second mixture; Step 4: Mix the first mixture and the second mixture to obtain a bio-based waterproof coating.
2. The bio-based waterproof coating according to claim 1, characterized in that: The preparation process of the coating base is as follows: Palm oil, formic acid and hydrogen peroxide are placed in a stirring device at a mass ratio of 1:0.21-0.25:0.45-0.55, treated at 55-60°C for 6-7 hours, and after solid-liquid separation, vacuum distillation is performed to obtain a preliminary product; The preliminary product and ethylene glycol are placed in a mixing device at a mass ratio of 1:0.7-0.9, and itaconic acid is added thereto. The mixture is stirred at 22-32°C and 80-110 r / min for 20-30 minutes, and then the temperature is raised to 140-150°C and constant temperature treatment is performed for 120-130 minutes to prepare a coating base material.
3. The bio-based waterproof coating according to claim 2, characterized in that: The added amount of itaconic acid is 3.2-3.5% of the base material mass.
4. The bio-based waterproof coating according to claim 1, characterized in that: The preparation process of the functional filler is as follows: The wheat straw is soaked in a sodium hydroxide aqueous solution with a mass concentration of 5.2-6.2% for 22-24 hours, then washed with deionized water for 2-6 times, and dried to obtain pretreated wheat straw; r-aminopropyltriethoxysilane is placed in a 90% ethanol aqueous solution at a mass ratio of 1:8-10, stirred at 100-120 r / min for 20-30 min to obtain a mixed solution, and then the composite material is added to the mixed solution, and ultrasonic treatment is performed for 30-40 min; Then, the pretreated wheat straw is added, and the ultrasonic treatment is continued for 25 to 35 minutes. After filtration, the mixture is dried and crushed to obtain a functional filler.
5. The bio-based waterproof coating according to claim 4, characterized in that: The composite material is prepared by mixing nano silicon dioxide and nano graphene oxide in a mass ratio of 1:0.2-0.
4.
6. The bio-based waterproof coating according to claim 4, characterized in that: The added amount of the composite material is 12-16% of the mass of the mixed liquid.
7. The bio-based waterproof coating according to claim 1, characterized in that: The preparation process of the synergistic filler is as follows: The bentonite is soaked in water for 50 to 60 minutes, filtered, dried to constant weight, and then placed in a resistance furnace, calcined at 510 to 530° C. for 120 to 140 minutes, cooled to 80° C., and kept warm for 40 minutes to obtain pretreated bentonite; The pretreated bentonite is placed in a sodium tripolyphosphate solution with a mass concentration of 12-14% at a solid-liquid ratio of 0.2-0.8 g / mL and mixed evenly, and allowed to stand at 70°C for 80-100 minutes. After filtration, the solution is dried to constant weight to obtain a synergistic filler.
8. The bio-based waterproof coating according to claim 1, characterized in that: The curing agent is selected from any one of toluene diisocyanate and diphenylmethane diisocyanate.
9. The bio-based waterproof coating according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant 1010, antioxidant 1076, and antioxidant CA.
Citation Information
Patent Citations
Method for preparing polyol by bio-oil one-kettle method and use of polyol
CN104311420A
Vegetable oil based polyurethane / silicon dioxide nano composite material and preparation method thereof
CN104327236A
Preparation method for vegetable oil polyhydric alcohols, vegetable oil polyhydric alcohols and application
CN104945256A
Flame-retardant insulating varnish with high paint film hardness and preparation method thereof
CN107987664A
Polyurethane anticorrosive coating for walls and preparation method of coating
CN108913005A
